The Role of School Environment and Its Influence on Students' Discipline and Politeness Character in Primary School Students - Novi Rosita Rahmawati; Prio Utomo (Indonesian Journal of Character Education Studies, 2024)
Background: The character development of discipline and politeness in primary school students is significantly influenced by various factors, one of which is the school environment. A conducive and well-managed school environment can shape students' attitudes and behaviors in a positive direction. Objective: The study aims to determine whether the school environment influences the formation of discipline and politeness character of primary school students. Method: This study employs an associative causal research design. The research was conducted at SD Islam AL Falih Kota Kediri in 2021. The population consisted of 30 4th-grade students, selected using a total sampling technique. Data were collected using discipline and politeness character scales, and analyzed using simple linear regression analysis. Result: The findings reveal a significant influence of the school environment (X) on the formation of students’ discipline character (Y), with a significance value (Sig.) of 0.001, which is less than 0.05. This indicates that the school environment plays a significant role in shaping students' discipline and politeness. Conclusion: There is a statistically significant relationship between the school environment and the development of discipline and politeness character in primary school students. Contribution: This study serves as valuable input and enrichment material for educators on the importance of fostering a positive school environment to support the development of students' discipline and polite behavior through various school-based strategies and settings.